Issue Information TOC. Issue 1 (17th September 2019) - Unknown
Abstract : Cover : In Yamamoto et al. (http://doi.org/10.1002/cpnc.99 ), the image shows molecular design of trivalent GalNAc ligands. (A ) A conventional trivalent pyramidal structure, (B ) our truncated‐pyramidal structure, (C ) a structure of tandemly‐conjugated monovalent GalNAc units we developed earlier (Yamamoto, Sawamura, Wada, Harada‐Shiba, & Obika, 2016).